2013
DOI: 10.1155/2013/409375
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical and Spectroscopic Characterization of Aluminium(III)-para-methyl-meso-tetraphenylporphyrin Complexes Containing Substituted Salicylates as Axial Ligands

Abstract: A series of aluminium(III)-p-methyl-meso-tetraphenylporphyrin (p-CH3TPP-Al(III)) containing axially coordinated salicylate anion [p-CH3TPP-Al-X)], where X = salicylate (SA), 4-chlorosalicylate (4-CSA), 5-chlorosalicylate (5-CSA), 5-flourosalicylate (5-FSA), 4-aminosalicylate (4-ASA), 5-aminosalicylate (5-ASA), 5-nitrosalicylate (5-NSA), and 5-sulfosalicylate (5-SSA), have been synthesized and characterized by various spectroscopic techniques including ultraviolet-visible (UV-vis), infrared (IR) spectroscopy, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…However, in the case of the ZnTPP-and Al(III)TPP-graphene hybrid layers, a noticeable change in the relative intensities and positions of the Q-bands was observed. Furthermore, only two Q-band absorption peaks appeared in the ZnTPP-and Al(III)TPP-graphene spectra due to the higher symmetry of the molecular species [39,40]. These results confirmed that ZnTPP and Al(III)TPP were successfully formed on the graphene surface.…”
Section: Experimental and Resultssupporting
confidence: 52%
“…However, in the case of the ZnTPP-and Al(III)TPP-graphene hybrid layers, a noticeable change in the relative intensities and positions of the Q-bands was observed. Furthermore, only two Q-band absorption peaks appeared in the ZnTPP-and Al(III)TPP-graphene spectra due to the higher symmetry of the molecular species [39,40]. These results confirmed that ZnTPP and Al(III)TPP were successfully formed on the graphene surface.…”
Section: Experimental and Resultssupporting
confidence: 52%
“…Recently, 2‐nitro‐5,10,15,20‐tetrakis(pentafluorophenyl)porphyrin ( 90 ) was obtained with an acceptable yield of 50%, by nitration of the proper substrate with indium nitrite In(NO 2 ) 3 , in a mixture of acetic acid anhydride and acetic acid followed by decomplexation (Scheme 31). [87] The above product was prepared for enzymatic investigations.…”
Section: Nitration Of Porphyrin Derivatives At the β‐Positionsmentioning
confidence: 99%
“…This reaction has been extensively studied and experimental procedures for selective mono-b-nitration were developed for a wide variety of porphyrins bearing meso-aryl substituents at the macrocycle periphery. [19][20][21][22][23][24][25][26][27][28][29] Among different synthetic procedures developed for the nitration of meso-tetraarylporphyrins, the treatment of free base porphyrins with copper(II) nitrate in the presence of acetic anhydride seems to be the most convenient and general procedure. 19 In fact, the reactivity of each porphyrin in 2H-1 series under these conditions was somewhat different but after optimization of the reagent amount, the temperature and the reaction time, all 2-nitroporphyrins Cu-4(a-f) were obtained in good to high yields (Scheme 2, 68-84%) (see ESI, † Table S1).…”
Section: B-aminoporphyrins and Their Transformationsmentioning
confidence: 99%
“…We have studied the preparation of these modular systems from available mesotetraarylporphyrins 2H-1 focusing our studies on the mild procedures tolerated by different functional groups (Scheme 1). In this regard, mono b-aminoporphyrins 2H-2 seem to be attractive intermediate compounds because of their ready availability from meso-tetraarylporphyrins 2H-1 by using nitration, [19][20][21][22][23][24][25][26][27][28][29][30] followed by the reduction of the nitro group. 21,[31][32][33][34][35][36] Scheme 1 briefly summarizes different synthetic approaches to modular porphyrins from 2-aminoporphyrins 2H-2.…”
Section: Introductionmentioning
confidence: 99%